Clinical Characteristics Analysis of 1051 Cases of Cleft Lip With/Without Cleft Palate in the Ethnic Tibetan Population - Duan, Shijun; Zheng, Qian; Shi, Bing; Feng, Fan (Sichuan da xue xue bao. Journal of Sichuan University. Yi xue ban, 2024)
To examine the characteristics of the prevalence of congenital cleft lip with/without cleft palate in the ethnic Tibetan population and to provide support for the precise prevention and treatment of cleft lip with/without cleft palate in the Tibetan population. The clinical data of Tibetan patients with cleft lip with/without cleft palate were collected and the clinical characteristics of the patients were analyzed. The patients' age ranged from 2 months to 51 years old. All the subjects were admitted to West China Stomatology Hospital, Sichuan University for the treatment of cleft lip with/without cleft palate between January 2016 and August 2023. Most of the subjects came from Sichuan Province and the Tibet Autonomous Region. A total of 1051 patients were enrolled and children aged under 12 months (460 cases) accounted for the largest proportion. Among the subjects, 383 had cleft lip only (36.44%), 140 had cleft palate only (13.32%), and 528 had cleft lip with cleft palate (50.24%). The male-to-female ratio